2011
DOI: 10.4081/ijas.2011.e37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the partial substitution of fish meal by soy bean meal with or without mannanoligosaccharide and fructooligosaccharide on the growth and feed utilization of sharpsnout seabream,Diplodus puntazzo(Cetti, 1777): preliminary results

Abstract: The present study was carried out in order to investigate the effects of the mannanoligosaccharide (MOS) and fructooligosaccharide (FOS) on sharpsnout seabream, Diplodus puntazzo in the context of partial fish meal substitution by soybean meal. One-hundredforty-four sharpsnout seabream of about 100 g initial body weight were randomly divided in 12 experimental tanks (180 litre each). Testing conditions included 12 fish per tank, with triplicate tanks for treatment. The experimental period lasted 114 days. Aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The present study demonstrated that dietary MOS or inulin did not significantly affect the growth performance of fish. This was also observed in the first part of the trial (Piccolo et al, 2011). Taking into account the SGR, it resulted obviously similar to the previous results.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The present study demonstrated that dietary MOS or inulin did not significantly affect the growth performance of fish. This was also observed in the first part of the trial (Piccolo et al, 2011). Taking into account the SGR, it resulted obviously similar to the previous results.…”
Section: Discussionsupporting
confidence: 80%
“…The techniques used for larval rearing are the same as those used for Sparus aurata (Marangos, 1995) and relative high hatching and survival rates at first feeding permit obtaining appropriate percentage of juveniles . The results of research are quite encouraging, and indicate a considerable increase in sharpsnout seabream production in the near future (Orban et al, 2000;Hernàndez et al, 2001;Favaloro et al, 2002;Bonaldo et al, 2004;Piccolo et al, 2011).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations